2013
DOI: 10.1038/pr.2013.236
|View full text |Cite
|
Sign up to set email alerts
|

Systemic glycerol decreases neonatal rabbit brain and cerebellar growth independent of intraventricular hemorrhage

Abstract: Background Cerebellar hypoplasia is common problem for preterm infants, and infants that suffer intraventricular hemorrhage (IVH). To evaluate the effects of IVH on cerebellar growth and development, we used a neonatal rabbit model of systemic glycerol to produce IVH. Methods New Zealand White rabbit kits were surgically delivered 2 d preterm, and treated with i.p. glycerol (3.25 to 6.5 g/kg). Controls were born at term. IVH was documented by ultrasound. Brain MRI volumes, cerebellar foliation, proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Since both groups were equally affected, we speculate that glycerol, which has been shown to be greatly increased (1.7 mM) following triheptanoin infusion [13], could contribute to the hemorrhage. High concentration of glycerol given systemically induce intraventricular and subarachnoid hemorrhage in neonatal rabbit models [35,36]. These findings suggest that care should be taken if considering administering lipidbased parenteral nutrition to stroke patients.…”
Section: Discussionmentioning
confidence: 93%
“…Since both groups were equally affected, we speculate that glycerol, which has been shown to be greatly increased (1.7 mM) following triheptanoin infusion [13], could contribute to the hemorrhage. High concentration of glycerol given systemically induce intraventricular and subarachnoid hemorrhage in neonatal rabbit models [35,36]. These findings suggest that care should be taken if considering administering lipidbased parenteral nutrition to stroke patients.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, in order to understand how GMH impacts NSPC and cortical development in the intermediate group, in whom outcomes appear to be most variable and who may have the most to gain from intervention, a more subtle injury model is needed. Currently available physiological techniques [52] cannot be used to model low-grade GMH as it causes widespread haemorrhage within the brain parenchyma [50] and may also be confounded by the use of glycerol, which has been shown to impact cortical development independently [54] . Similarly, the interpretation of results following the injection of collagenase into the SVZ [25] , whilst reducing bolus size, is significantly limited due to the potentially confounding affect of collagenase on the NSPC.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: We read the Traudt et al (1) article with interest, in which the authors reported their experience with our glycerol model of intraventricular hemorrhage (IVH). The authors found a much higher mortality rate and a lower incidence of IVH in the glycerol-treated E29 rabbit pups compared to our report published in 2008 (2).…”
mentioning
confidence: 99%
“…The number of P12 survivors were 7, 3, and 5 in 3.25, 4.87, and 6.5 g/kg glycerol dose groups, respectively (their Table 1) and of these, three pups with IVH were excluded from evaluation (1). In view of the small sample size of each group, unknown birthweight and growth of animals, and a presumably sick group of Correspondence Ballabh and LaGamma pups exhibiting high mortality, the authors' conclusion might be premature.…”
mentioning
confidence: 99%